A lobe-specific lymphadenectomy protocol for solitary pulmonary nodules in non-small cell lung cancer - Yang, Xue-Ning; Zhao, Ze-Rui; Zhong, Wen-Zhao; Nie, Qiang; Liao, Ri-Qiang; Dong, Song (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2014)
Objectives: We want to establish a lobe-specific mediastinal lymphadenectomy protocol for solitary pulmonary nodules (SPNs) in non-small cell lung cancer (NSCLC). Methods: We retrospectively analyzed 401 patients with pathological diagnoses of NSCLC who underwent lobectomy, bilobectomy, or pneumonectomy with systematic lymphadenectomy from March 2004 to June 2011 in our hospital. All of the patients enrolled had a SPN preoperatively. Information about the primary tumor location, lymph node metastasis, and other baseline data were collected. Stepwise logistic regression was used to identify the key factors indicating non-regional mediastinal lymph node metastases (NRM). Results: Of the primary tumors, 117, 39, 74, 104, and 67 were in the right upper lung (RUL), right middle lung (RML), right lower lung (RLL), left upper lung (LUL), and left lower lung (LLL), respectively. Stepwise regression showed that #2,4, #10,11, and #10,11 as well as #7 was the key lymph node station for RUL, LUL, and lower lobes: #2,4 [odds ratio (OR)=28.000, 95% confidence interval (CI): 2.917-268.790, P=0.004] for RUL, #10,11 (OR=31.667, 95% CI: 2.502-400.833, P=0.008) for LUL, #10,11 (OR=19.540, 95% CI: 4.217-90.541, P2 cm rarely had NRM without primary regional mediastinal involvement. Conclusions: With rigid consideration, a lobe-specific lymphadenectomy is feasible in practice. This protocol can be used when the lobe-specific key nodes are negative in intraoperative frozen sections, especially for NSCLC diagnosed as SPN